Hubungan Pendampingan Suami dengan Kecemasan Ibu Bersalin Normaldi Ruang Siti Hajar RSI Sultan Hadlirin Jepara - Titik Lutfiana; Ratna Ratna; Akbar Amin Abdullah (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
On May 20, 2025, researchers conducted a preliminary study in the delivery room and it was found that there were 30 mothers giving birth. From the interview results, it was found that there were three mothers who were not accompanied by their husbands, but by their parents, because their husbands were working and therefore could not be present. Mothers who were not accompanied by their husbands admitted to feeling anxious and worried about bad possibilities during the delivery process. In contrast, three mothers who were accompanied by their husbands expressed feeling more enthusiastic and calm because of the direct support from their partners. This study aims to determine the relationship between husband's assistance and the level of anxiety of mothers giving birth normally in the Siti Hajar Room of RSI Sultan Hadlirin Jepara. The type of research is quantitative with a correlational design. The study population included all mothers giving birth normally in the Siti Hajar Room in July 2025 with a total of 30 respondents. The sampling technique used was total sampling, while the research instrument was a HARS (Hamilton Anxiety Rating Scale) questionnaire that had been tested for validity and reliability. Data analysis used the Chi-Square test. The results showed that the majority of mothers gave birth accompanied by their husbands (70%), and most experienced mild anxiety (46.7%). The statistical test yielded an Asymp Sig value of 0.007 <0.05. Thus, it was concluded that there was a significant relationship between husband's support and maternal anxiety levels during childbirth..   Keywords: anxiety, childbirth, husband's suppor   Abstrak. Pada tanggal 20 Mei 2025, peneliti melakukan studi pendahuluan di ruang bersalin dan diketahui terdapat 30 ibu bersalin. Dari hasil wawancara diperoleh bahwa terdapat tiga ibu yang tidak didampingi oleh suami, melainkan oleh orang tua, karena suami bekerja sehingga belum bisa hadir. Ibu yang tidak didampingi suami mengaku merasa cemas dan khawatir akan kemungkinan buruk saat proses persalinan. Sebaliknya, tiga ibu yang didampingi suami menyampaikan perasaan lebih semangat dan tenang karena adanya dukungan langsung dari pasangan.Penelitian ini bertujuan untuk mengetahui hubungan pendampingan suami dengan tingkat kecemasan ibu bersalin normal di Ruang Siti Hajar RSI Sultan Hadlirin Jepara. Jenis penelitian adalah kuantitatif dengan desain correlational. Populasi penelitian meliputi seluruh ibu bersalin normal di Ruang Siti Hajar pada bulan Juli 2025 dengan jumlah 30 responden. Teknik sampling yang digunakan adalah total sampling, sedangkan instrumen penelitian berupa kuesioner HARS (Hamilton Anxiety Rating Scale) yang telah diuji validitas dan reliabilitas. Analisis data menggunakan uji Chi Square.Hasil penelitian menunjukkan mayoritas ibu bersalin didampingi suami (70%), dan sebagian besar mengalami kecemasan ringan (46,7%). Uji statistik menghasilkan nilai Asymp Sig = 0,007 < 0,05. Dengan demikian, disimpulkan terdapat hubungan signifikan antara pendampingan suami dengan tingkat kecemasan ibu dalam menghadapi persalinan. Kata kunci:kecemasan,persalinan,pendampingan suami